Entomopathogenic nematology in Latin America: A brief history, current research and future prospects - San Blas, Ernesto (2019)
Since the 1980s, research into entomopathogenic nematodes (EPNs) in Latin America has produced many remarkable discoveries. In fact, 16 out of the 117 recognized species of EPNs have been recovered and described in the subcontinent, with many more endemic species and/or strains remaining to be discovered and identified. In addition, from an applied perspective, numerous technological innovations have been accomplished in relation to their implementation in biocontrol. EPNs have been evaluated against over 170 species of agricultural and urban insects, mites, and plant-parasitic nematodes under laboratory and field conditions. While much success has been recorded, many accomplishments remain obscure, due to their publication in non-English journals, thesis dissertations, conference proceedings, and other non-readily available sources. The present review provides a brief history of EPNs in Latin America, including current findings and future perspectives.